Vickers Indentation Cracking of Ion-Exchanged Glasses: Quasi-Static vs. Dynamic Contact - Gross, Timothy M.; Price, James J. (Frontiers in Materials, 2017)
The indentation deformation and cracking responses of ion-exchanged glasses were measured using quasi-static and dynamic loading cycles. Two glass types were compared, a normal glass that deforms to a large extent by a shearing mechanism and a damage resistant glass that comparatively deforms with less shear and more densification. The quasi-static indentation cracking threshold for median/radial cracks for the ion-exchanged normal glass was determined to be 7 kilograms force (kgf), while the ion-exchanged damage resistant glass required loads exceeding 30 kgf. The increased cracking threshold of the damage resistant glass composition is attributed to the deformation mechanism, i.e. deformation with greater densification/less shear results in less subsurface damage and less residual stress. Both glass types were also subjected to dynamic indentation where the contact event time was more than 10,000 times shorter than the quasi-static condition. Under dynamic loading conditions, the cracking thresholds of the ion-exchanged normal and damage resistant glasses increased to greater than 50 kgf and greater than 150 kgf, respectively. The stress induced optical retardation was compared for quasi-static and dynamic indents made at sub-cracking threshold loads for both glasses. For indents made at the same sub-cracking threshold load in the normal glass, optical retardation mapping indicates less residual stress surrounding dynamic indents when compared to quasi-static indents. This suggests a rate dependence on the deformation mechanism in normal glasses with higher rates promoting densification in favor of shear. However, for damage resistant glass, the stress induced optical retardation is the same for indents made at both quasi-static and dynamic indentation rates.